Metabolic Variability of a Multispecies Probiotic Preparation Impacts on the Anti-inflammatory Activity - Biagioli, Michele; Laghi, Luca; Carino, Adriana; Cipriani, Sabrina; Distrutti, Eleonora; Marchianò, Silvia; Parolin, Carola; Scarpelli, Paolo; Vitali, Beatrice; Fiorucci, Stefano (Frontiers in Pharmacology, 2017)
Background. In addition to strain taxonomy, the ability of probiotics to confer beneficial effects on the host rely on a number of additional factors including epigenetic modulation of bacterial genes leading to metabolic variability and might impact on probiotic functionality. Aims. To investigate metabolism and functionality of two different batches of a probiotic blend commercialized under the same name in Europe in models of intestinal inflammation. Methods. Boxes of VSL#3, a probiotic mixture used in the treatment of pouchitis, were obtained from pharmacies in UK subjected to metabolomic analysis and their functionality tested in mice rendered colitis by treatment with DSS or TNBS. Results. VSL#3-A (lot DM538), but not VSL#3-B (lot 507132), attenuated “clinical” signs of colitis in the DSS and TNBS models. In both models, VSL#3-A, but not VSL#3-B, reduced macroscopic scores, intestinal permeability and expression of TNFα, IL-1β and IL-6 mRNAs, while increased the expression of TGFβ and IL-10, occludin and zonula occludens-1 (ZO-1) mRNAs and shifted colonic macrophages from a M1 to M2 phenotype (P<0.05 versus TNBS). In contrast, VSL#3-B, failed to reduce inflammation and worsened intestinal permeability in the DSS model (P<0.001 versus VSL#3-A). A metabolomic analysis of the two formulations allowed the identification of two specific patterns, with at least 3 folds enrichment in the concentrations of four metabolites, including 1-3 dihydroxyacetone (DHA), an intermediate in the fructose metabolism, in VSL#3-B supernatants. Feeding mice with DHA, increased intestinal permeability. Conclusions. Two batches of a commercially available probiotic show divergent metabolic activities. DHA, a product of probiotic metabolism, increases intestinal permeability, highlighting the complex interactions between food, microbiota, probiotics and intestinal inflammation.